Enhancing Natural Killer Cell Targeting of Pediatric Sarcoma - Omer, Natacha; Nicholls, Wayne; Ruegg, Bronte; Souza-Fonseca-Guimaraes, Fernando; Rossi, Gustavo Rodrigues (Frontiers in Immunology, 2021)
Osteosarcoma, Ewing sarcoma (EWS), and rhabdomyosarcoma (RMS) are the most common pediatric sarcomas. Conventional therapy for these sarcomas comprises neoadjuvant and adjuvant chemotherapy, surgical resection of the primary tumor and/or radiation therapy. Patients with metastatic, relapsed, or refractory tumors have a dismal prognosis due to resistance to these conventional therapies. Therefore, innovative therapeutic interventions, such as immunotherapy, are urgently needed. Recently, cancer research has focused attention on natural killer (NK) cells due their innate ability to recognize and kill tumor cells. Osteosarcoma, EWS and RMS, are known to be sensitive to NK cell cytotoxicity in vitro. In the clinical setting however, NK cell cytotoxicity against sarcoma cells has been mainly studied in the context of allogeneic stem cell transplantation, where a rapid immune reconstitution of NK cells plays a key role in the control of the disease, known as graft-versus-tumor effect. In this review, we discuss the evidence for the current and future strategies to enhance the NK cell-versus-pediatric sarcoma effect, with a clinical focus. The different approaches encompass enhancing antibody-dependent NK cell cytotoxicity, counteracting the NK cell mechanisms of self-tolerance, and developing adoptive NK cell therapy including chimeric antigen receptor-expressing NK cells.